Parasuicidality and paradox : breaking through the medical model - Ellenhorn, Ross D. (Springer Pub., 2008)
In the United States, over 1/4 of all psychiatric emergency room visits each year are for chronically acute behaviors often labeled "parasuicidal," leading to a continuous loop of complaints and ineffective interventions. This book offers an effective way out. It introduces a theory that radically departs from current ideas about such behaviors.